2012
DOI: 10.4172/2165-7920.1000192
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Giant Lipoma in Right Loin

Abstract: Lipoma is one of the commonest benign mesenchymal tumors in body and found almost in all organs where the fat exists. It is usually small but giant lipomas can be present in thigh, shoulder and trunk. The present study describes a 46 year old male with a huge mass right loin which on histopathology revealed features suggestive of lipoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…2 Venkatachalapathy, Sreeramulu and Prathima have reported a case report of giant lipoma in right loin. 6 They didn't suggest about any dimensions of mass in this study. Jen-Chih Huang et al have reported giant axillar lipoma.…”
Section: Discussionmentioning
confidence: 72%
“…2 Venkatachalapathy, Sreeramulu and Prathima have reported a case report of giant lipoma in right loin. 6 They didn't suggest about any dimensions of mass in this study. Jen-Chih Huang et al have reported giant axillar lipoma.…”
Section: Discussionmentioning
confidence: 72%